2000
DOI: 10.1074/jbc.275.20.15413
|View full text |Cite
|
Sign up to set email alerts
|

Cystine Knot Mutations Affect the Folding of the Glycoprotein Hormone α-Subunit

Abstract: The common glycoprotein hormone ␣-subunit (GPH-␣) contains five intramolecular disulfide bonds, three of which form a cystine knot motif (10 -60, 28 -82, and 32-84). By converting each pair of cysteine residues of a given disulfide bond to alanine, we have studied the role of individual disulfide bonds in GPH-␣ folding and have related folding ability to secretion and assembly with the human chorionic gonadotropin ␤-subunit (hCG-␤). Mutation of non-cystine knot disulfide bond 7-31, bond 59 -87, or both (leavin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…5 Because the ␣-helix apparently increases the stability of this part of the structure, the disulfide bond Cys-21-27 itself would not be essential for the conformational stability of AVR4. Similar observations were previously reported for the cystine-knot fold (46 AVR4 (des-species). AVR4 and the des-species were trapped to chitin before incubation with apoplastic fluid.…”
Section: Figsupporting
confidence: 80%
“…5 Because the ␣-helix apparently increases the stability of this part of the structure, the disulfide bond Cys-21-27 itself would not be essential for the conformational stability of AVR4. Similar observations were previously reported for the cystine-knot fold (46 AVR4 (des-species). AVR4 and the des-species were trapped to chitin before incubation with apoplastic fluid.…”
Section: Figsupporting
confidence: 80%
“…Previous studies have revealed the importance of the disulfide bridges for the folding of glycoprotein hormone ␣-subunit in vivo (30). Here we showed that in vitro, it is possible to generate cystine-deficient mutants of the cystine knot growth factor VEGF and to subsequently investigate their crystal structures.…”
Section: Function Of the Cystine Knot In Vegfmentioning
confidence: 90%
“…Unfortunately, comparisons with other growth factors cannot be drawn because to the best of our knowledge, no thermodynamic characterization of a cystine knot growth factor has been reported to date. Data on the function of the individual disulfide bridges in these growth factors are restricted to observations on impaired expression in mammalian cells (30), as well as to measurements of residual biological activity in mutants in which single cysteines have been removed (31,32).…”
Section: Enthalpic and Entropic Contributions To ⌬Gmentioning
confidence: 99%
“…Oxidative folding has now been studied for representatives of all three subfamilies of cystine knots, namely the inhibitory cystine knots (12,14,15), the growth factor knots (36,37), and the cyclic cystine knot (20), and the present study is the first report on the oxidative folding of a representative of the trypsin inhibitor subfamily of CCK. Some studies have reported that the cystine knot is either necessary for folding or has a role in directing the folding (36,37), but that it is not required for the overall thermodynamic stability of the protein (37).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that the cystine knot is either necessary for folding or has a role in directing the folding (36,37), but that it is not required for the overall thermodynamic stability of the protein (37). Several reports have also emphasized that the cystine knot is a structural feature that governs the exceptional thermal (as opposed to thermodynamic) stability of proteins containing it (22,37).…”
Section: Discussionmentioning
confidence: 99%